Leadership of Pesantren in the Management of Human Resources Production - Halid, Ahmad (Journal of Pesantren and Diniyah Studies, 2024)
This article examines the leadership process in Islamic boarding schools (pesantren) in managing the production of excellent human resources. Superior pesantren resources are produced through transcendental activities, commitment to traditional pesantren scholarly traditions and transmissions, internalization of moral exemplarity, and playing a role in empowering education and social transformation in the community. This research uses a descriptive qualitative approach, sharpening phenomenological research by describing the general meaning of several cases in pesantren based on the various life experiences of pesantren residents. The data collection methods for this research include interviews, observations, artifacts, autoethnography, and focus groups. This research aims to study the production of pesantren human resources. The results of this study are: first, pesantren leadership produces educated individuals who can carry out Islamic preaching (da'wah Islamiah) and provide services or guidance to the community to become knowledgeable, faithful, morally upright, responsible individuals with an awareness of the importance of life for the hereafter. Second, pesantren leadership educates students and the community to acquire various life skills as a foundation for independent living.